Interplay of internal stresses, electric stresses, and surface diffusion in polymer films - Closa, Fabien; Ziebert, Falko; Raphaël, Elie (Physical review. E, Statistical, nonlinear, and soft matter physics, 2011)
We investigate two destabilization mechanisms for elastic polymer films and put them into a general framework: first, instabilities due to in-plane stress and, second, due to an externally applied electric field normal to the film’s free surface. As shown recently, polymer films are often stressed due to out-of-equilibrium fabrication processes such as, e.g., spin coating. Via an Asaro-Tiller-Grinfeld mechanism as known from solids, the system can decrease its energy by undulating its surface by surface diffusion of polymers and thereby relaxing stresses. On the other hand, application of an electric field is widely used experimentally to structure thin films; when the electric Maxwell surface stress overcomes surface tension and elastic restoring forces, the system undulates with a wavelength determined by the film thickness. We develop a theory taking into account both mechanisms simultaneously and discuss their interplay and the effects of the boundary conditions both at the substrate and at the free surface.
Gesehen am 23.09.2022